ANXIETY OF FINAL STUDENTS WHO HAVE NOT YET STARTED THEIR THESIS IN FACING THE QUESTION 'WHEN WILL THEY GRADUATE?': SELF-EFFICACY ANALYSIS - Siti Putri Astuti; Nuril Hidayanti S (LP2M IAI Al-Khairat Pamekasan, 2026)
Final year students often experience academic stress, pressure from family, and increased anxiety when facing the demands of preparing a thesis. This study aims to understand the dynamics of academic anxiety experienced by final year students who have not yet started preparing their thesis, especially when facing social questions about their academic progress. This study uses a qualitative approach with a case study design for one subject from the class of 2020 who experienced difficulties in starting a thesis due to academic pressure, family expectations, and negative experiences from others. Data were collected through in-depth interviews, non-participant observations, and document analysis related to the subject's academic behavior. Data analysis was carried out with a thematic approach based on four sources of self-efficacy, according to Bandura. The results showed that the subjects' low self-efficacy was related to a lack of experience of academic success, negative experiences from family members who did not complete their studies, a lack of motivational verbal support, as well as physiological and emotional conditions characterized by excessive anxiety. Social questions like